Genetic admixture of Kruger National Park black rhino (Diceros bicornis minor): conservation implications - Stanbridge, Deborah (Department of Biological Sciences, 2021)
Black rhinoceroses (Diceros bicornis) have been extirpated from most of their historic range with the remaining individuals (ca. 5200) living in geographically isolated populations. Management priorities include creating new populations whilst maintaining genetic diversity and promoting gene flow between existing isolated populations. Such objectives are however currently hindered by a lack of comparative/reference data on levels of diversity, relatedness and inbreeding in a large, free-ranging black rhinoceros population. Here I attempt to address this gap in our knowledge by investigating the genetic diversity of the black rhinoceros Diceros bicornis minor within Kruger National Park (the largest free-ranging population of this subspecies) using nuclear and mitochondrial DNA. I compared the diversity of this founded population with the two source populations (KwaZulu-Natal, South Africa and Zimbabwe) using published studies, and evaluate the relative contribution of source lineages relative to the proportion of original founders. Analysis of the mtDNA control region revealed four haplotypes, with moderate haplotype and nucleotide diversity (h=0.48 (± 0.05 SD); π= 0.29%). Data from 13 microsatellite loci revealed moderate to high levels of genetic variation (number of alleles = 4.92 ± 0.90, effective number of alleles = 2.26 ± 0.25, observed heterozygosity = 0.50 ± 0.04, expected heterozygosity = 0.51 ± 0.04), low mean pairwise relatedness (r = -0.03), a low inbreeding coefficient (Fis = 0.04) and no evidence of genetic structuring. Diversity levels within the Kruger black rhinoceros population were high compared to levels reported in black rhinoceroses originating in KwaZulu-Natal and similar to those reported in individuals originating in Zimbabwe. Results show that 40-60% of the Zimbabwean lineages are represented in the Kruger population which is a noticeable increase in the relative contribution of the Zimbabwe founder population. The data provided by this study can be used to guide management and conservation decisions regarding maximising genetic variability across the subspecies. Furthermore, given the encouraging levels of genetic diversity observed, the Kruger black rhinoceros population would be an ideal source population for supplementation of genetically depauperate populations or creating new populations. Finally, these findings demonstrate a positive outcome in mixing the KwaZulu-Natal and Zimbabwe gene pools, with evidence that the founder Kruger black rhinoceros population has been genetically rescued from the low diversity seen in the KwaZulu-Natal black rhinoceroses in South Africa.